IMPLEMENTASI ARSITEKTUR PEMROGRAMAN MICROSERVICES UNTUK MIGRASI SISTEM INFORMASI PT. DWIDAYA WORLD WIDE (DWIDAYA TOUR AND TRAVEL) DENGAN METODOLOGI SDLC RAPID APPLICATION DEVELOPMENT - Wisnu Sukma Maulana (Asosiasi Dosen Muda Indonesia, 2022)
Dwidaya Tour has a fairly rapid business development both branches in almost all of Indonesia and the services they offer to the public ranging from train tickets, planes, Umrah, and all services in the field of travel. Problems arise when all services and branches have their respective systems and are not connected and centralized. Thus, Dwidaya tour wants a rapid migration into one centralized system without stopping all of the systems that are running. The purpose of this study is the result of implementing the solution used to overcome these problems. The use of the microservices programming architecture for the migration process. Where microservices architecture allows each stand-alone system to be a service at the back-end level and connected to a centralized system at the front-end level. Because the migration process needed must be fast, the SDLC (System Development Life Cycle) approach based on the RAD (Rapid Application Development) methodology was used. This RAD methodology has a stage of user evaluation involvement as a key means for the development and deployment process to be more precise and short in duration for its development.